¿Reparar lo imperdonable?: Sobre justicia restaurativa y violencia sexual = Repairing the Irreparable? : On Restorative Justice and Sexual Violence - Bernuz Beneitez, María José (Revista de victimología, 2025)
The basic goal of restorative justice (RJ), whose most well-known tool is penal mediation, is the meaningful reparation of the victim and the effective accountability of the offender. Although the 2012 Directive of the European Parliament and the Spanish Victim Statute (2015) established rules to ensure victims’ access to RJ services, its implementation in Spain is very limited, among other circumstances, due to the prohibition of using mediation in cases of gender-based violence (established by Organic Law 1/2004), which Organic Law 10/2022 has extended to cases of sexual violence. This article provides a critical review of the regulations and doctrines regarding the reasons for such prohibitions. We understand that there are three main explanatory hypotheses: A paternalistic view that limits the freedom and possibilities of reparation for victims, which is combined with a demonizing view of the offender as irredeemable; an erroneous conception of penal mediation understood as a lesser justice for minor cases ; and a homogenization of all cases of sexual violence classified as unforgivable.